The Sign of the Gospel : toward an evangelical doctrine of infant baptism after Karl Barth - McMaken, W. Travis (Minneapolis : Fortress Press, 2013)
The theology of the sacraments is one of the most contested parts in Barth's theology, none more so than the doctrine of baptism. Barth's proposals on baptism have generated intense conversation and disagreement, not only on its application to Protestant and ecumenical theology but even on its own consistency with Barth's larger dogmatic project. McMaken takes up this controversial question, sets it in its proper context within the history of doctrine and Barth's systematic work, and argues for a constructive reclamation of infant baptism that accords with Barth's overarching theological concerns.
Baptism and infant baptism from the New Testament through Barth -- Election, soteriology, and Barth's "no" to sacramental infant baptism -- Election, circumcision, and Barth's "no" to covenantal infant baptism -- Barth's doctrine of baptism, the foundation of the Christian life -- The sign of the Gospel : toward a post-Barthian doctrine of infant baptism.
Includes bibliographical references (p. 287-314) and indexes.
Keywords: Barth, Karl, -- 1886-1968.; Bible. -- Theology; Infant baptism; Theology, Doctrinal